The Effect of Corporate Governance on Firm Value Mediated by Earnings Quality - Lukman Lukman; Sindi Claudia Sambur; Ana Mardiana (Magister Akuntansi - Universitas Atma Jaya Makassar, 2024)
This research aims to analyze the effect of corporate governance on corporate value with earnings quality as mediating variable. The population used in this study is manufacturing companies listed on the Indonesia Stock Exchange within 2019 to 2021. The theories used are agency theory and stakeholder theory. Total population in this study is 157 companies. The sample selected with purposive sampling technique, that 56 sample companies was obtained. The analysis used in this study is path analysis with Sobel testing. Results of this study show that first hypothesis is rejected because the audit committee has a negative and significant effect on earnings quality, the second hypothesis is accepted because the Board of Directors has a positive and significant effect on earnings quality, the third hypothesis is rejected because earnings quality has a negative effect and significant to firm value, the fourth hypothesis is accepted because earnings quality able to mediate the influence of the audit committee on firm value and the fifth hypothesis is accepted because earnings quality is able to mediate the influence of the board of directors on firm value.